Polish dialect kinship names according to the data in Volume 11. "Degrees of Kinship" of the Slavic Linguistic Atlas (preliminary results in a comparative perspective) - Keremidchieva, Slavka (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2023)
The article discusses data on kinship names in Polish dialects on the basis of an analysis of 82 linguistic maps and the comments to them from Volume 11. “Degrees of Kinship,” which has been prepared for publication by the Bulgarian National Commission as part of the lexical-word-formation series of the Slavic Linguistic Atlas. The language material is authentic, collected and verified on site by Polish dialectologists and includes terms for biological kinship and for relation by marriage and by matchmaking. Special attention is paid to the similarities and contrasts between Polish dialects and East and South Slavic dialects, on the one hand, and the Polish language and the other West Slavic languages, on the other. Emphasis is placed on kinship names that belong to the all- Slavic vocabulary, as well as the expansion of foreign language loanwords and elements that have completely replaced the native lexis. With nomina affinitatis, the disintegration of the old original naming system and the emergence of differences in the Slavic language territory can be traced. The research has employed linguo- geographical and comparative methods.